Current noise in single-molecule junctions induced by electronic-vibrational coupling - Schinabeck, Christian; Härtle, Rainer; Weber, Heiko B.; Thoss, Michael (Physical Review B, 2014)
The influence of multiple vibrational modes on current fluctuations in electron transport through single molecule junctions is investigated. Our analysis is based on a generic model of a molecular junction, which comprises a single electronic state on the molecular bridge coupled to multiple vibrational modes and fermionic leads, and employs a master equation approach. The results reveal that in molecular junctions with multiple vibrational modes, already weak to moderate electronic-vibrational coupling may result in high noise levels, especially at the onset of resonant transport, in accordance with the experimental findings of Secker et al. [Phys. Rev. Lett. 106, 136807 (2011)]. The underlying mechanisms are analyzed in some detail.
UnivIS-Import:2015-04-14:Pub.2014.nat.dphy.IAP.LAP.curren